Carcass and parts yield of broilers reared under a semi-extensive system - Faria,PB (2010)
An experiment was carried out to evaluate carcass traits of male and female broilers of two genetic strains (Paraíso Pedrês and Pescoço Pelado), slaughtered at 65, 75, 85 and 95 days of age, and reared under a semi-extensive production system. The following parameters were evaluated: body weight at slaughter (BWs), carcass weight (CW), carcass yield (CY), parts yield, including breast, drumstick, thighs, back, neck, feet, wings, abdominal fat pad (AF), and giblets (gizzard, heart, liver). Paraíso Pedrês males presented higher BWs and CW. Paraíso Pedrês females had higher breast yield. Thighs and drumstick yields were higher in Pescoço Pelado males. Back yield was similar at 85 and 95 days of age, wing yield declined with age. AF yield was higher in Paraíso Pedrês and in females. GY was affected by sex and slaughter age. The results of this work lead to the conclusion that Paraíso Pedrês males reach higher live and carcass weights at 85 and 95 days of age, and that breast yield is higher in this strain. On the other hand, Pescoço Pelado males present higher drumstick and thighs yields. Therefore, the choice of genetic strain, sex and slaughter weight will determine carcasses with different parts yield.